Design of online platform and visualization system based on three-dimensional spatial information for occupant satisfaction with indoor environment quality. Issue 4 (September 2019) - Lee, Jongwon; Kim, Deuk-Woo
Abstract: Prior evaluations of building energy performance have focused on quantitative performance based on mathematical models while overlooking the value of quality of residential life. The Post-Occupancy Evaluation (POE) method is regarded as an important component of the value judgment process for enhancing the quality of actual building performance. Accordingly, we developed a cost-effective open-source survey platform to collect data on occupant satisfaction. This study focuses on the evaluation indexes of indoor environment quality (IEQ) and conducted a pilot test. The difference of this platform compared with existing online survey systems is that the survey information is linked with the shape and spatial information of the building. This study's online platform for surveying occupant satisfaction is expected to significantly reduce the time and costs required for conventional IEQ occupant satisfaction surveys. In addition, the collected survey responses are analyzed through a database and visualized as a prototype based on 3D spatial information, providing more intuitive feedback to the owner and occupants of the building.